Clinical experience with cyclosporine eye drops for severe dry eye - O.I. Lebedev; A.V. Surov; E.V. Akentieva (РМЖ "Клиническая офтальмология")
O.I. Lebedev1, A.V. Surov1, E.V. Akentieva2 1Omsk State Medical University, Omsk, Russian Federation 2Clinical Ophthalmologic Hospital named after V.P. Vykhodtsev, Omsk, Russian Federation Dry eye disease provokes inflammation of autoimmune origin. Therefore, immunosuppressants are pathogenetically reasonable for this disorder. Topical 0.05% cyclosporine emulsion may provide good treatment outcomes when tear replacement drops and corneal protective remedies are ineffective. Cyclosporine is a calcineurin inhibitor which blocks T cells thus decreasing pro-inflammatory cytokine release and preventing goblet cell apoptosis. This paper describes clinical experience with cyclosporine in a woman with severe dry eye who received long-term treatment without stable favorable outcomes. Topical 0.05% cyclosporine emulsion (eye drops) improves subjective signs and functional test results as well as provides corneal infiltrate epithelialization. The analysis of clinical sings and functional test results demonstrates that cyclosporine is highly effective for severe dry eye which manifests with corneal and conjunctival inflammation and degeneration (especially considering autoimmune origin of the inflammation). In addition, this agent provides favorable outcomes when standard tear replacement and anti-inflammatory treatment is ineffective. Key words: dry eye, xerosis, autoimmune inflammation, apoptosis, goblet cells, anti-inflammatory treatment, cyclosporine. For citation: Lebedev O.I., Surov A.V., Akentieva E.V. Clinical experience with cyclosporine eye drops for severe dry eye. Russian Journal of Clinical Ophthalmology. 2019;19(1):50–53. About the authors: 1Оleg I. Lebedev — MD, PhD, Professor, Head of Ophthalmological Department; 1Aleksandr V. Surov — MD, PhD, Associate Professor of Ophthalmological Department; 2Yevgeniya V. Akentyeva — ophthalmologist. 1Omsk State Medical University. 12, Lenin str., Оmsk, 644099, Russian Federation. 2Clinical Ophthalmologic Hospital named after V.P. Vykhodtsev. 60, Lermontov str., Оmsk, 644024, Russian Federation. Contact information: Aleksandr V. Surov, e-mail: abc55.79@mail.ru. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received: 18.09.2018.